SCENARIO APPROACH TO CHOOSING A STRATEGY FOR FINANCIAL SUPPORT OF THE MAIN COMPONENTS OF NATIONAL SECURITY - Мединська Тетяна Володимирівна; Ruslan Skrynkovskyy; Petro Senyk; Zinaida Zhyvko; Nataliia Rak (ТОВ «ФІНТЕХАЛЬЯНС», 2025)
The article defines a comprehensive approach to financing components of national security, covering the military, economic, social and energy spheres. The importance of a balanced distribution of resources, based on quantitative and qualitative analysis, in particular on econometric models and expert assessments, is proven. The feasibility of using a scenario approach, which includes modelling possible options for system transitions between different states, considered discrete-time chains, is substantiated. It is established that simultaneous attention to comprehensive monitoring, control mechanisms and regulatory framework contributes to a more efficient use of financial resources and reduces vulnerability to external and internal threats. It is established that the successful activation of mechanisms for financing components of security involves a preliminary assessment of priorities, strategic planning, interdepartmental coordination, regular monitoring and adjustment. It is substantiated that such an approach ensures sustainable growth, minimizes domestic political risks and creates a basis for effective cooperation with international partners. As a result, the article proves the vital need for a comprehensive, systematic and flexible financial policy aimed at protecting the long-term interests of the state in the context of modern challenges to national security.
СЦЕНАРНИЙ ПІДХІД ДО ВИБОРУ СТРАТЕГІЇ ФІНАНСОВОГО ЗАБЕЗПЕЧЕННЯ ОСНОВНИХ СКЛАДОВИХ НАЦІОНАЛЬНОЇ БЕЗПЕКИ
Financial and Credit Activity Problems of Theory and Practice, 2025. 3(62), p. 418-428
Keywords: national security financing; discrete-time chains; balanced resource allocation; interagency coordination; econometric models; scenario forecasting; strategic planning